Herbs Used as Antidiabetic : A Review - Ubrusun, Jufri; Suharjono, Suharjono; Novrianti, Irma (Ad-Dawaa' Journal of Pharmaceutical Sciences, 2021)
Diabetes mellitus is a syndrome characterized by a condition of hyperglycemia, and changes in the metabolism of lipids, carbohydrates, and proteins. Diabetes mellitus is characterized by an increase in glucose levels caused by insulin deficiency either in absolute or relative terms. Diabetes mellitus therapy is a long-term therapy and is relatively expensive. Therefore, it is necessary to look for effective alternative drugs with low prices such as herbal medicines derived from plants. Indonesia is one of the countries that has a diversity of plants, so many plants that grow in Indonesia can be used as an alternative therapy to overcome diabetes mellitus. This paper aims to provide a relevant review of medicinal plants used for diabetes mellitus that has been carried out in research on tested animals. This research was conducted by searching for national and international articles from the internet, which were searched from 2011 to 2019, including original articles, and experimental articles, about Traditional medicine for diabetics. The following keywords are used : [[ “studi in vivo tumbuhan obat untuk diabetes” OR “Uji efektifitas ekstrak tumbuhan sebagai antidiabetik” OR “tumbuhan sebagai antidiabetik” ]] OR [["Test extract activity against diabetic mice" OR "antidiabetic plant" OR "antidiabetic herbal medicine" OR "antidiabetic in rat”, “Traditional medicine of diabetisin Indonesia” ]]. From the results of the literature study, it was found that 21 articles with 24 medicinal plants were tested in vivo on test animals to reduce blood sugar in diabetes mellitus. These medicinal plants contain compounds of the type of flavonoids, alkaloids, tannins, saponins, polyphenols, terpenoids, and phenolics that can have a therapeutic effect on decreasing blood sugar levels in test animals.